E-inclusion for seniors - online learning programs for older adults - Lipphardt, Anne-Marie; Esteller-Curto, R.; Fowley, Cathy; Papitto, Patrizia; Issakainen, Cecil (5th International conference on the elderly and new technologies, 2017)
This paper sums up the evaluation results of an e-learning ICT course for older adults inexperienced in using ICT and discusses possibilities and limits of online learning in general. As part of the European project EHLSSA (European Home Learning Service for Seniors Association), online course modules were developed to teach older adults basics in computer usage and in going online. In the first run 40 participants (age range 60-86 y.) from Germany and Spain participated in the online course. After the course run, feedback could be gathered in the form of a questionnaire with both open and close questions. The evaluation focused on satisfaction with the learning progress, course content and support during the course run. Additionally, questions on the appropriateness of e-learning for teaching this kind of content were posed to the participants. The results show that e-learning is a highly suitable learning method for older adults. Particularly the possibility to arrange learning time flexibly and to repeat content as often as necessary was positively highlighted by the participants. Even the preparation of content for ICT-beginners and applicability in the everyday life was assessed as successful. Social contact with other participants was not rated particularly high, but was at the same time not considered to be relevant for this kind of courses. In general, many respondents indicated that they wish that the offer of online courses for older adults will be extended and that they would like to participate in online courses in the future again. <
Keywords: e-learning; older adults; ICT course